Micro waqf bank and its impact on micro-enterprise productivity in Indonesia - Vanni, Kartika Marella (Journal of Islamic Economics Management and Business (JIEMB), 2023)
This study aims to examine the mechanisms and schemes implemented by micro waqf bank (Bank Wakaf Mikro, BWM) in enhancing the productivity of micro-enterprises in Indonesia. Using a descriptive qualitative methodology with a literature review approach, this research analyzes secondary data from various relevant academic sources. The findings indicate that BWM combines the concept of waqf with microfinance services, which includes the collection of cash waqf funds through Islamic banks, waqf institutions, and digital platforms. Fund management is conducted by nāẓir who invests the funds in sharia-compliant instruments to support BWM operations and microfinance programs. The financing schemes used by BWM include qarḍ al-ḥasan, muḍārabah, mushārakah, and productive waqf. The qarḍ al-ḥasan scheme provides interest-free loans, while the muḍārabah and mushārakah schemes involve partnerships in business management with profit-sharing based on agreed ratios. The productive waqf scheme utilizes waqf assets to generate income used for microfinance. The implementation of these schemes requires collaboration with various parties and innovations in digital technology to enhance efficiency and transparency. Overall, BWM has provided inclusive financial access, improved micro-enterprise capacity, and created a sustainable business ecosystem for micro-enterprises in Indonesia.